Analisis Penyelenggaraan Sistem Pemeliharaan Alat Radiologi Rsu Royal Prima Medan - Kewin Gozali; Ermi Girsang; Putranto Manalu (Universitas Pahlawan Tuanku Tambusai, 2026)
Hospitals as providers of professional, high-quality, and sustainable health services require adequate support from standardized medical equipment, including in the radiology unit. Radiology equipment must be systematically maintained to ensure optimal functionality, produce accurate diagnostic results, and foster patient satisfaction as well as positive public perceptions of the hospital. This study aimed to analyze the implementation of the radiology equipment maintenance system at RSU Royal Prima Medan. This research employed a qualitative design, with primary data obtained through in-depth interviews with relevant informants. Data analysis was conducted using triangulation, followed by data reduction, data presentation, and conclusion drawing. The results showed that, in terms of input, the maintenance of radiology equipment at RSU Royal Prima Medan was supported by the availability of adequate and functional facilities and infrastructure, a sufficient number of human resources, and personnel with appropriate expertise and knowledge according to their respective roles and responsibilities. The maintenance budget was available, although the exact amount was not clearly specified. In terms of process, maintenance activities were carried out routinely, including daily cleaning and comprehensive inspections every six months to assess equipment feasibility. All maintenance procedures were implemented in accordance with the established Standard Operating Procedures (SOPs). In terms of output, all radiology equipment at RSU Royal Prima Medan was in good, normal, and operational condition, enabling accurate diagnostic examinations. In conclusion, the radiology equipment maintenance system at RSU Royal Prima Medan has been implemented effectively and in compliance with established SOPs.